The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s13753-012-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of threshold ranges for rapid flood inundation mapping by evaluating backscatter profiles of high incidence angle SAR images

Abstract: Rapid satellite-based flood inundation mapping and delivery of flood inundation maps during a flood event can provide crucial information for planners and decision makers to prioritize relief and rescue operations. The present study is undertaken to optimize the threshold ranges for the classification of flood water in Synthetic Aperture Radar (SAR) images (of 20° to 49° incidence angles) for quick flood inundation mapping and response during flood disasters. This is done through assessing the signature of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 11 publications
8
91
0
1
Order By: Relevance
“…Modes that have large extents (beyond 70 km) are available in one or two polarizations (HH and HV or VV and VH), due to the storage and downlink capacity of the satellite, while smaller swaths can provide all four polarizations. Previous studies [5,20] had shown that HH is the preferred polarization for mapping flooded vegetation, because it maximizes canopy penetration and enhances the contrast between forest and flooded vegetation. Also, HH has lower backscatter over rough open water (roughness induced by wind) than VV, and therefore is better to map open water under windy conditions.…”
Section: Image Acquisition and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Modes that have large extents (beyond 70 km) are available in one or two polarizations (HH and HV or VV and VH), due to the storage and downlink capacity of the satellite, while smaller swaths can provide all four polarizations. Previous studies [5,20] had shown that HH is the preferred polarization for mapping flooded vegetation, because it maximizes canopy penetration and enhances the contrast between forest and flooded vegetation. Also, HH has lower backscatter over rough open water (roughness induced by wind) than VV, and therefore is better to map open water under windy conditions.…”
Section: Image Acquisition and Parametersmentioning
confidence: 99%
“…Due to its all-weather capabilities, and its image acquisition capacity during day or night or in cloudy conditions, SAR imagery offers better alternatives for water mapping than optical imagery [5]. As a result of the radar's unique response to water, water mapping using intensity thresholding methods on SAR image had been extensively used [4][5][6][7]20,21]. In this method, water is separated from land in intensity images, but the accuracy of the results relies on the ability to differentiate land vs. water pixels in the intensity domain, which becomes especially difficult when the water backscatter is affected by wind-induced roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SAR images are effective for extracting inundation areas. Several methods, both pixel-and object-based, have been proposed to extract inundation zones from SAR images (Martinis, 2009 and2015;Hoque et al, 2011;Manjusree et al, 2012;Pulvirenti et al, 2014;Kundu et al, 2015;Nakmuenwai et al, 2017). Thresholding is a 5 common and effective pixel-based approach.…”
Section: Thresholding Methods For Water Regionmentioning
confidence: 99%
“…Thresholding is a 5 common and effective pixel-based approach. It is difficult to judge the most suitable value objectively in manual thresholding; therefore, automated thresholding methods have been introduced to overcome this issue (Fan and Lei, 2009;Martinis, 2009 and2015;Manjusree et al, 2012). In this study, the threshold value for water was investigated automatically using reference areas.…”
Section: Thresholding Methods For Water Regionmentioning
confidence: 99%
See 1 more Smart Citation